2000
DOI: 10.1067/mpr.2000.106873
|View full text |Cite
|
Sign up to set email alerts
|

In vitro dentinal surface reaction of 9.5% buffered hydrofluoric acid in repair of ceramic restorations: A scanning electron microscopic investigation

Abstract: Topical application of hydrofluoric acid appeared to provide a dentinal surface with an amorphous precipitate of fluoride. This layer may be important both for resistance of dental caries in dentin and for bonding reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…This is supported by the TEM results, where extensive accumulation of silver deposits was observed in the porous hybrid layers following the application of PB and OB to oxalate-treated dentin. Similar effects have recently been reported following the application of hydrofluoric acid gel to acid-etched dentin (Szep et al, 2000;Pioch et al, 2003).…”
Section: Discussionmentioning
confidence: 55%
“…This is supported by the TEM results, where extensive accumulation of silver deposits was observed in the porous hybrid layers following the application of PB and OB to oxalate-treated dentin. Similar effects have recently been reported following the application of hydrofluoric acid gel to acid-etched dentin (Szep et al, 2000;Pioch et al, 2003).…”
Section: Discussionmentioning
confidence: 55%
“…Similar interference has recently been reported following the application of hydrofluoric gels to acid-etched dentine. 47,48 Unlike the calcium oxalate crystals that were formed 10-15 mm beneath the calcium-depleted dentine surface, 8,9 these interfering surface and subsurface globular structures ( Fig. 4B and C) did not provide a seal of the dentinal tubules.…”
Section: Discussionmentioning
confidence: 90%
“…Also, HF can severely traumatize tooth structure . Szep et al . found that HF leaves a layer of amorphous fluoride deposit on the tooth surface that interferes with the process of bonding and acid etching.…”
Section: Discussionmentioning
confidence: 99%
“…Also, HF can severely traumatize tooth structure. 3,24 Szep et al 25 found that HF leaves a layer of amorphous fluoride deposit on the tooth surface that interferes with the process of bonding and acid etching. Several studies have stated that this method cannot be applied in clinical dental practice especially for intraoral ceramic repair.…”
Section: Discussionmentioning
confidence: 99%